Dissemination of an Electronic Manual to Build Capacity for Implementing Farmers’ Markets with Community Health Centers - Guest, M. Aaron (Clin Transl Sci, 2015)
Community–university partnerships can lend themselves to the development of tools that encourage and promote future community health development. The electronic manual, “Building Farmacies,” describes an approach for developing capacity and sustaining a community health center–based farmers’ market that emerged through a community–university partnership. Manual development was guided by the Knowledge to Action Framework and experiences developing a multivendor, produce‐only farmers’ market at a community health center in rural South Carolina. The manual was created to illustrate an innovative solution for community health development. The manual was disseminated electronically through 25 listservs and interested individuals voluntarily completed a Web‐based survey to access the free manual. During the 6‐month dissemination period, 271 individuals downloaded the manual. Findings highlighted the value of translating community‐based participatory research into user‐friendly manuals to guide future intervention development and dissemination approaches, and demonstrate the need to include capacity building opportunities to support translation and adoption of interventions.